PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA PADA KINERJA MELALUI SEMANGAT KERJA PEGAWAI PADA KANTOR DESA SE KECAMATAN RANGSANG PESISIR - Ardianto; Indra Prasetyo; Mei Indrawati (Journal of Applied Management and Accounting Science, 2021)
he purpose of this study was to describe the conditions of organizational culture, job satisfaction, work morale, and employee performance at the Village Office in Rangsang Pesisir District. To determine the effect of organizational culture and job satisfaction on employee performance through morale in the Village Offices in Rangsang Pesisir District. The approach in this research is a quantitative approach. The population in this study were all Village Office Employees in Rangsang Pesisir District. The sample in this study was 94 people consisting of employees in 11 villages in Rangsang Pesisir District. Data collection with questionnaires and documentation and data analysis methods by testing the validity and reliability and using path analysi. The results showed that organizational culture, job satisfaction, morale, and performance of Village Office Employees in Rangsang Pesisir District were all in good condition. Organizational culture and job satisfaction have a significant effect on both work enthusiasm and employee performance. work spirit also has a significant influence on employee performance. organizational culture and job satisfaction have a significant effect on employee performance through morale.